2006
DOI: 10.3949/ccjm.73.9.821
|View full text |Cite
|
Sign up to set email alerts
|

Is digoxin a drug of the past?

Abstract: Digoxin has been the cornerstone of the treatment of heart failure for more than 2 centuries. Now that newer therapies have been introduced that reduce the mortality rate in heart failure and recent trials have failed to prove the same for digoxin, its use has significantly decreased. But a careful review of the multiple pharmacologic actions of digoxin and closer analysis of the results of recent trials suggest that digoxin may in fact continue to be an effective treatment for heart failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
35
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 34 publications
0
35
0
1
Order By: Relevance
“…CTSs such as digoxin and digitoxin are still an important component of the clinical treatment of cardiac diseases (26,65). CTSs were discovered in digitalis plants and amphibian tissues (25,75).…”
mentioning
confidence: 99%
“…CTSs such as digoxin and digitoxin are still an important component of the clinical treatment of cardiac diseases (26,65). CTSs were discovered in digitalis plants and amphibian tissues (25,75).…”
mentioning
confidence: 99%
“…It has been speculated that the retrospective subgroup analysis that suggested the increased risk may have been related to higher mean digoxin levels among women compared to men. A more recent analysis using a multivariate Cox proportional hazards regression model found that at lower serum concentrations (0.5-0.9 ng/mL), digoxin did not increase mortality in women [8]. Moreover, low serum digoxin concentrations in women decreased the risk of hospitalization for worsening HF and the combined endpoint of mortality due to HF and HF hospitalization.…”
Section: Digitalismentioning
confidence: 99%
“…So, it seems clear then that if digoxin is going to be used, it should be given in a dose to achieve a serum digoxin concentration between 0.5 and 0.9 ng/mL given the limited evidence currently available [8]. In particular, the serum digoxin concentration achieved in the RADIANCE Trial was 1.2 ng/mL and in the DIG Trial it was 0.8 ng/dL [7].…”
Section: Digitalismentioning
confidence: 99%
See 2 more Smart Citations